Bifid Nose: Case presentation - Lugo-Machado, Juan Antonio (2021)
Objetive: A bifid nose is a rare congenital anomaly that occurs during embryological development of the nose. In 1939, Esser published a series of 11 cases. Case Report: Here we present the case of a girl who was born with a forked nose that was managed with a tracheostomy to secure the airway. Later, at 6 months of age, she underwent a first intervention to improve the external appearance of the nose.